Portowiec . biuletyn informacyjny, no. 20a, 1981 - [temporary ed. Jerzy Albiniak et al.., graphic design by KH Henryk Kaczmarczyk], Niezależny Samorządny Związek Zawodowy "Solidarność" (KZ NSZZ "Solidarność" Zarządu Portu Gdańsk, 1981)
Creation and circulation: Publication suspended after the introduction of the Martial Law. Issues no. 57(1983)-nr 145(1989) published underground. From issue no. 146(1990) published again legally; Logo: ZP Gdańsk